Developing an intervention program based on attachment to God and investigating its effectiveness on ineffective spiritual schemas and spiritual well-being - Nazari, Mohammad.; Ghobari Bonab, Bagher; Bahrinan, Seyed Abdul Majid; Haji Alizadeh, Kobra (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: Inefficient spiritual patterns of our adaptation to God’s laws cause problems in the society in living environments, the present study aims to formulate an intervention program based on attachment to God and examine its effectiveness on ineffective spiritual patterns and spiritual well-being. Methods: From a methodological point of view, the current research was a quasi-experimental research design with a pre-test-post-test with a control group. The statistical population of this research was made up of all employees of Continental Plateau Oil Company in 2019. The sample of this study was 60 people who were randomly selected in two experimental and control groups (20 people in each subgroup) based on the criteria of entering and exiting the study. The research tool was the questionnaire of ineffective spiritual schemas, attachment to God and spiritual well-being, which was completed by all participants in the pre-test and post-test phases. God attachment sessions were held for experimental group participants in nine 120-minute sessions, while control group participants did not receive any intervention. Research data were analyzed using multivariate analysis of covariance and using SPSS-22 software. Results: The results showed that the intervention based on the quality of attachment to God has an effect on all the components of ineffective spiritual schemas and spiritual well-being (P<0.01). Conclusion: According to the results of this study, the intervention based on the quality of attachment to God led to the improvement of all the components of ineffective spiritual schemas and spiritual well-being